Projecting sensations to external objects: evidence from skin conductance response - Armel, K. Carrie; Ramachandran, V. S. (Proceedings of the Royal Society B : Biological Sciences, 2003)
Subjects perceived touch sensations as arising from a table (or a rubber hand) when both the table (or the rubber hand) and their own real hand were repeatedly tapped and stroked in synchrony with the real hand hidden from view. If the table or rubber hand was then 'injured', subjects displayed a strong skin conductance response (SCR) even though nothing was done to the real hand. Sensations could even be projected to anatomically impossible locations. The illusion was much less vivid, as indicated by subjective reports and SCR, if the real hand was simultaneously visible during stroking, or if the real hand was hidden but touched asynchronously. The fact that the illusion could be significantly diminished when the real hand was simultaneously visible suggests that the illusion and associated SCRs were due to perceptual assimilation of the table (or rubber hand) into one's body image rather than associative conditioning. These experiments demonstrate the malleability of body image and the brain's remarkable capacity for detecting statistical correlations in the sensory input.